2019
DOI: 10.1017/s0031182019000374
|View full text |Cite
|
Sign up to set email alerts
|

Impact of levamisole in co-administration with benznidazole on experimental Chagas disease

Abstract: Levamisole (Lms) is an anthelminthic drug with immunomodulatory activity. Chagas disease (CD) is caused by Trypanosoma cruzi and there is very low access to the drugs available, benznidazole (Bz) and nifurtimox, both far from ideal. In a drug-repurposing strategy to test potential activity as antiparasitic and immunomodulatory agent for CD, Lms was assayed on acute T. cruzi murine infection, alone and in co-administration with Bz. During protocol standardization, 100 and 10 mpk of Bz given for five consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…According to these results, which indicated NOAEL > 200 mg kg −1 for both compounds – some solubility problems observed with compound 24 led to NOAEL > 100 mg kg −1 when given ip (Supplementary Table S1), different protocols were applied administering to T. cruzi -infected mice non-toxic doses of 25 mg kg −1 , as mono- and combined therapy with BZ. The reference drug was also given in suboptimal doses of 25 mg kg −1 , which correspond to 1/4 of the regimen standardized for this model of acute infection: BZ optimal doses of 100 mg kg −1 completely suppress the parasitaemia of T. cruzi Y-infected Swiss Webster mice, either with two unique administrations (de Araújo et al ., 2014; Timm et al ., 2014) or five consecutive daily doses (Fonseca-Berzal et al ., 2014; Timm et al ., 2014; da Silva et al ., 2017; Simões-Silva et al ., 2017, 2019). According to this, the administration of both derivatives and BZ in such a low dosage allows better comparison among the impact of these experimental treatments over T. cruzi infection (Martín-Escolano et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these results, which indicated NOAEL > 200 mg kg −1 for both compounds – some solubility problems observed with compound 24 led to NOAEL > 100 mg kg −1 when given ip (Supplementary Table S1), different protocols were applied administering to T. cruzi -infected mice non-toxic doses of 25 mg kg −1 , as mono- and combined therapy with BZ. The reference drug was also given in suboptimal doses of 25 mg kg −1 , which correspond to 1/4 of the regimen standardized for this model of acute infection: BZ optimal doses of 100 mg kg −1 completely suppress the parasitaemia of T. cruzi Y-infected Swiss Webster mice, either with two unique administrations (de Araújo et al ., 2014; Timm et al ., 2014) or five consecutive daily doses (Fonseca-Berzal et al ., 2014; Timm et al ., 2014; da Silva et al ., 2017; Simões-Silva et al ., 2017, 2019). According to this, the administration of both derivatives and BZ in such a low dosage allows better comparison among the impact of these experimental treatments over T. cruzi infection (Martín-Escolano et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Considering all the results obtained in vivo , these monotherapy protocols conducted with both 5-nitroindazole derivatives did not lead to better effectiveness than BZ; however, the co-administration schemes showed superior anti-parasitic profile than the reference drug. Recently, other pre-clinical studies have revealed important findings of trypanocidal effectiveness in vivo by co-administering different compounds with the reference drug BZ (Guedes-da-Silva et al ., 2019; Simões-Silva et al ., 2019). The implementation of combined therapies is an alternative actually considered for the treatment of CD (Sales Junior et al ., 2017; Ribeiro et al ., 2020), and already in clinical use for combating many illnesses, including those triggered by parasitic infections, such as malaria (WHO, 2015) and sleeping sickness (WHO, 2019), among others.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological analysis showed fewer tissue lesions and parasite infiltratesTorrico F et al (2018)E1224 (a water-soluble ravuconazole prodrug)HumanE1224 displayed a transient, suppressive effect on parasite clearance, whereas benznidazole showed early and sustained efficacy until 12 months of follow-up.Guedes-da-Silva et al (2019)Sterol 14α-Demethylase (Inhibitor VFV)Benznidazole (Antiprotozoal)Swiss Webster miceparasitemia suppression and 100% animal survival Coadministration of Bz + VFV (resulted in 106-fold lower blood parasitism as compared to the monotherapy of Bz)De Araújo et al (2019)Imidazole Derivatives and Benznidazole (Antiprotozoal)MRC -5 cells and Primary cardiac cellsPotent and selective activity against T. cruzi Rial et al, 2019Allopurinol (Antigout) and Benznidazole (Antiprotozoal)C57BL/6J and C3H/HeN miceabsence of electrical abnormalities, significant reductions in antibody titres and parasitic loadsMazzeti et al, 2019Allopurinol combined with benzinidazole (Antiprotozoal) or Nifurtimox (Antiprotozoal)Mammalian cell, Swiss miceThe interactions were synergic. Administration of the drugs in combination increased the cure rate.Rocha et al (2019)Levamisole (anthelminthic)Benznidazole (Antiprotozoal)Swiss Webster miceIn vivo: The association partially reduced parasitemia and did not increased animal survivalND* not determined.…”
Section: Drug Associationmentioning
confidence: 99%
“…155 Table 4 shows other promising drug associations for the treatment of experimental T. cruzi infection. 87,90,154,164,[183][184][185][186][187][188][189][190][191][192][193][194]…”
Section: Dovepressmentioning
confidence: 99%
“…BNZ/levamisole Monotherapies of levamisole did not decrease parasitemia nor mortality rates. In combinations with a low dose of BNZ, it led to a slight improvement in the effectiveness of monotherapy [192] BNZ/NFX Combining shorter treatments could cure mice, but the association led to the behavioral alterations of treated mice.…”
Section: Bnz/voriconazolementioning
confidence: 99%